The Impact of School Operational Assistance Program Implementation at School Level on Senior Secondary Education Enrollment by Households: Evidence from Indonesia in 2007 and 2014 - Kartasasmita, Fairuzah Pertiwi; Sulistyaningrum, Eny (Economics and Finance in Indonesia, 2021)
Education is recognized worldwide as one of the key elements in developing the human capital of a nation for a prosperous future. Given an almost universal enrollment in primary education, many governments have shifted their focus on students motivation to continue to and finish their secondary education. The government of Indonesia has made extensive efforts in widening participation in education. With a growing budget for educational expenditure, various government programs have been implemented to assist students in their learning. One such program is the School Operational Assistance Program (BOS), which has been running for two decades. This paper reports on a study aimed to investigate the impact of the implementation of BOS at a school level on senior secondary school enrollment by households using data obtained from the Indonesia Family Life Survey (IFLS) recorded in 2007 and 2014. By using Propensity Score Matching (PSM), it was found that students whose schools received BOS during their primary education years were more likely to continue their education to senior secondary education than those whose schools did not receive BOS. This shows that a school subsidy could encourage students to continue their education, particularly for students coming from poorer households.